PENGARUH MODEL PEMBELAJARAN KUANTUMUNTUK MENINGKATKANKEPERCAYAAN DIRI SISWA PADA MATA PELAJARAN PPKN - Tenggon, Tenggon; Rosyid, Rum; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purpose of this study was to find out how much influence the use of quantum learning models on student confidence in PPKn class X subjects at SMK Negeri 03 Pontianak. In carrying out this research using experimental research methods with a quantitative approach. Variable X uses the quantum learning model, while the Y variable is student confidence. The subjects in this study were class X PM1 as an experimental class and XPM2 class as a control class. Analyzing the results of research using SPSS 16.0 and Microsoft Excel programs. The results of this study indicate the difference between the experimental class and the control class, the average confidence of students in the experimental class 69.7 with the category